# How do you solve #4x^2-13x+3=0#?

##### 2 Answers

#### Explanation:

**Use the quadratic formula.**

**Solve for #x#.**

Solve: y = 4x^2 - 13x + 3 = 0

Answers: 1/4 and 3

#### Explanation:

Use the new Transforming Method (Google and Yahoo Search)

Transformed equation: y' = x^2 - 13x + 12. Both roots are positive.

Factor pairs of ac = 12 --> (1, 12) = 13.

y1 = 1 and y2 = 12

x1 = y1/a = 1/4 and x2 = y2/a = 12/4 = 3

Answers: 1/4 and 3.

**Note** : I advise students to learn and solve quadratic equations by the new Transforming Method. It is simpler and faster than using the formula or the factoring by grouping method.